The Rule of Law in Relation to Changing Criminal Legislation - Šepec, Miha (65 pravne znanosti v Mariboru, 2026)
The rule of law in criminal law is expressed in the fact that a law defining criminal offences or infringements of individual rights is adopted by the competent legislative body, and at the same time that the legal content reflects the fundamental constitutional principles of the rule of law. Since criminal law most invasively encroaches on the fundamental rights of individuals, it is essential that criminal legislation is adopted in cooperation with the profession. Legislation adopted by a politically motivated body outside the rules of the profession will practically always result in the adoption of an unconstitutional law. While the Constitutional Court, which corrects the legislator's mistakes, is provided for such cases, in the field of criminal law, additional guarantees must be provided to limit the adoption of unconstitutional legislation as much as possible. The consequences for individuals in the field of criminal regulations are significantly more severe for individuals than the consequences in other legal areas. The necessary and minimal protection is therefore that the criminal law profession participates in the adoption of changes to criminal legislation.